FANDOM


   Simplify 4 – 3[4 –2(6 – 3)] ÷ 2.
   I will simplify from the inside out: first the parentheses, then the square brackets, being careful to remember that the "minus" sign on the 3 in front of the brackets goes with the 3. Only once the grouping parts are done will I do the division, followed by adding in the 4.
       4 – 3[4 –2(6 – 3)] ÷ 2
           = 4 – 3[4 – 2(3)] ÷ 2
           = 4 – 3[4 – 6] ÷ 2
           = 4 – 3[–2] ÷ 2
           = 4 + 6 ÷ 2
           = 4 + 3
           = 7

Remember that, in leiu of grouping symbols telling you otherwise, the division comes before the addition, which is why this expression simplified, in the end, down to "4 + 3", and not "10 ÷ 2".


   Simplify 16 – 3(8 – 3)2 ÷ 5.
   I must remember to simplify inside the parentheses before I square, because (8 – 3)2 is not the same as 82 – 32.
       16 – 3(8 – 3)2 ÷ 5
           = 16 – 3(5)2 ÷ 5
           = 16 – 3(25) ÷ 5
           = 16 – 75 ÷ 5
           = 16 – 15
           = 1

If you have learned about variables and combining "like" terms, you may also see exercises such as this:

   Simplify 14x + 5[6 – (2x + 3)].
   If I have trouble taking a subtraction through a parentheses, I can turn it into multiplying a negative 1 through the parentheses (note the highlighted red "1" below):
       14x + 5[6 – (2x + 3)]
           = 14x + 5[6 – 1(2x + 3)]
           = 14x + 5[6 – 2x – 3]
           = 14x + 5[3 – 2x]
           = 14x + 15 – 10x
           = 4x + 15
   Simplify –{2x – [3 – (4 – 3x)] + 6x}.
   I need to remember to simplify at each step, combining like terms when and where I can:
       –{2x – [3 – (4 – 3x)] + 6x}
           = –1{2x – 1[3 – 1(4 – 3x)] + 6x}
           = –1{2x – 1[3 – 4 + 3x] + 6x}
           = –1{2x – 1[– 1 + 3x] + 6x}
           = –1{2x + 1 – 3x + 6x}
           = –1{2x + 6x – 3x + 1}
           = –1{5x + 1}
           = –5x – 1

(For more examples of this sort, review Simplifying with Parentheses.)

This next example displays an issue that almost never arises but, when it does, there seems to be no end to the arguing.

   Simplify 16 ÷ 2[8 – 3(4 – 2)] + 1.
       16 ÷ 2[8 – 3(4 – 2)] + 1
           = 16 ÷ 2[8 – 3(2)] + 1
           = 16 ÷ 2[8 – 6] + 1
           = 16 ÷ 2[2] + 1   (**)
           = 16 ÷ 4 + 1
           = 4 + 1
           = 5

The confusing part in the above calculation is how "16 divided by 2[2] + 1" (in the line marked with the double-star) becomes "16 divided by 4 + 1", instead of "8 times by 2 + 1". That's because, even though multiplication and division are at the same level (so the left-to-right rule should apply), parentheses outrank division, so the first 2 goes with the [2], rather than with the "16 divided by". That is, multiplication that is indicated by placement against parentheses (or brackets, etc) is "stronger" than "regular" multiplication.

Ad blocker interference detected!


Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.